Análise acústica comparativa das vogais orais entre respiradores orais e nasais - Oliveira, Luciana Regina de (2011)
Introduction: oral breathing (RO) can influence tongue movements patterns and this can cause persistent alterations in speech, chewing and swallowing throughout life. Studies show that the use of acoustic analysis allows us to infer tongue position during the production of speech. This can be helpful in the processes of diagnosis and speech therapy. Objectives: to present acoustic data of the formant patterns (frequency and intensity of the first three formants F1, F2 and F3, and the bandwidth of the first formant F1) of Brazilian Portuguese (PB) oral vowels as produced by individuals diagnosed with mouth breathing (RO) and individuals presenting no respiratory alterations (RN). Methodology: the corpus consisted of words, inserted in carrier sentences, containing all of the seven oral vowels in stressed position and semi-spontaneous speech. It was recorded by two groups of subjects (RO and RN). These two groups were further divided into two age groups (7-10 years and 10 years and one month to 12 years). Results: statistical differences between RO s and RN s vowel formants (frequency and intensity) have been found. The comparison between the vowel formant structures revealed that the F1 frequencies of the open vowels produced by the RO group were lower than those produced by the RN group, but the F2 frequencies were found to be lower in anterior vowels. These data can be interpreted as related to diminished tongue movement and jaw openness. The comparison among age groups (7 years -10 years and 10 years and 1 month 12 years) within RO and RN groups showed that all formant frequencies (F1, F2 and F3) of the vowels produced by the 7 -10 age group were higher than the older group. This finding can be interpreted as correlated to laryngeal and craniofacial growth. The intensity values of the vowels produced by the RO group were found to be higher than the ones produced by the RN group. This finding can to be correlated with the higher degrees of laryngeal tension (hyperfunction) which characterized RO s voice qualities and characteristics of oral cavity size due to high and narrowed palate area. Conclusion: comparison between the formant structures of the vowels produced by the RO and the RN groups were found to differ in terms of formant frequency (F1, F2 and F3) and intensity (I1, I2 e I3)